Chimeric antigen receptor‐modified T‐cell therapy for platelet‐derived growth factor receptor α‐positive rhabdomyosarcoma. (15th April 2020) - Xiao, Wei; Wang, Jinghua; Wen, Xizhi; Xu, Bushu; Que, Yi; Yu, Kuai; Xu, Liping; Zhao, Jingjing; Pan, Qiuzhong; Zhou, Penghui; Zhang, Xing
Abstract : Background: New immunotherapeutic approaches are urgently needed for metastatic rhabdomyosarcoma, which is associated with poor survival and unsatisfactory treatment outcomes. Platelet‐derived growth factor receptor α (PDGFRA) plays an essential role in the onset and development of rhabdomyosarcoma and is a new potential therapeutic target for rhabdomyosarcoma. The objective of this study was to generate humanized PDGFRA single‐chain variable fragment‐based chimeric antigen receptor (CAR)‐modified T cells (CAR‐T cells) against PDGFRA‐positive rhabdomyosarcoma. Methods: PDGFRA antigen expression was evaluated in specimens from patients with rhabdomyosarcoma. CAR‐T cells containing a PDGFRA‐specific single‐chain variable fragment was developed in combination with a 4‐1BB costimulatory domain and a CD3‐ζ signaling domain. Specific cytotoxic effects of PDGFRA CAR‐T cells, T‐cell proliferation, and cytokine secretion were investigated in vitro and in vivo. Results: PDGFRA CAR‐T cells produced large amounts of immune‐promoting cytokines, including interleukin 2, tumor necrosis factor α, and interferon γ, and exhibited efficient cytotoxic activity toward human PDGFRA‐overexpressing rhabdomyosarcoma cells in vitro. In a subcutaneous xenograft model, CAR‐T cells were more effective against PDGFRA‐overexpressing rhabdomyosarcoma than against rhabdomyosarcoma with low PDGFRA expression in terms of tumor regression and patient survival. Expanded CAR‐T cells also were detected in peripheral blood. Conclusions: The current study demonstrates for the first time that the PDGFRA antigen is a promising target for CAR‐T–cell therapy in rhabdomyosarcoma and likely in a wide spectrum of other PDGFRA‐expressing cancers. Abstract : New immunotherapeutic approaches are urgently needed for metastatic rhabdomyosarcoma, which is associated with poor survival and unsatisfactory treatment outcomes. The current study demonstrates that the platelet‐derived growth factor receptor α antigen is a promising target for chimeric antigen receptor‐modified T‐cell therapy in rhabdomyosarcoma and likely in a wide spectrum of other platelet‐derived growth factor receptor α‐expressing cancers.